Impact of Digital Adaptability and Work-Life Balance on Performance at Bank SMBC Cirebon - Rizki Fatullah; Siti Maryam (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the impact of digital adaptability and work-life balance on employee performance at PT Bank SMBC Area Cirebon. It seeks to understand how adapting to digital transformation and balancing professional and personal life contributes to optimizing human resource performance in the banking sector. The research employs a quantitative associative method with a survey approach. Primary data were collected directly through questionnaires distributed to 105 employees using a saturated sampling or census technique. Furthermore, the data were analyzed using multiple linear regression, including validity, reliability, and classical assumption tests, to determine the partial and simultaneous effects of the independent variables. The findings indicate that digital adaptability and work-life balance significantly influence employee performance. The adjusted R-square value shows that these variables contribute 53.8% to the variance in employee performance. In conclusion, higher digital adaptability and a balanced work-life dynamic lead to increased productivity and service quality. Practically, optimizing this performance supports the efficiency of financial intermediation, facilitating faster and more accurate financial access for MSMEs and individuals, thereby fostering a conducive environment for sustainable regional economic development and financial stability in the digital transformation era.